Pengembangan Media Pembelajaran Interaktif Berbantu Software iSpring terhadap Retensi Mahasiswa pada Konsep Kalkulus II - Shinta Dwi Handayani; Aulia Ar Rakhman Awaludin (Institut Agama Islam Negeri Curup, 2020)
The purpose of this study is to develop iSpring software aided interactive learning against student retention on the concept of calculus II. This type of research is RnD research. The development procedure, will be divided into 4 parts, namely preliminary analysis, implementation and preparation of learning media, validation and revision, and small-scale trials (limited). The sampling technique that I use is to use simple random sampling. The results show that there is a positive influence, student retention on student learning achievement in learning calculus II.